Conscious Thought and The Limits of Restrictivism - Marta Jorba (Crítica)
How should we characterize the nature of conscious occurrent thought? In the last few years, a rather unexplored topic has appeared in philosophy of mind: cognitive phenomenology or the phenomenal character of cognitive mental episodes. In this paper I firstly present the motivation for cognitive phenomenology views through phenomenal contrast cases, taken as a challenge for their opponents. Secondly, I explore the stance against cognitive phenomenology views proposed by Restrictivism, classifying it in two strategies, sensory restrictivism and accompanying states. On the one hand, I problematize the role of attention adopted by sensory restrictivism and I present and discuss in detail an argument that defends the limitation of sensory phenomenology so as to explain the distinction between visual and cognitive mental episodes on the basis of immediate experience. On the other hand, I address accompanying states views by discussing the empirical studies of Hurlburt et al. (2006, 2008) that defend the existence of “unsymbolized thinking”. I present how they can be construed as evidence for cognitive phenomenology views and I dispel some problems that have been raised against its acceptance. I thus conclude that cognitive phenomenology views hold up well against the restrictivist positions considered.